Intestinal celiac disease - related autoantibodies - Fontana, Giorgia; Ziberna, Fabiana; Barbi, Egidio; Di Leo, Grazia; De Leo, Luigina (Frontiers in Immunology, 2025)
Celiac disease is a widespread autoimmune enteropathy with a genetic predisposition triggered by gluten intake. The only available treatment is a strict lifelong gluten-free diet. The diagnosis is based on the detection of serum celiac disease - related antibodies and histopathological analysis of duodenal biopsies. However, celiac disease has a wide spectrum of clinical, histological, and serological manifestations, and in some patients, the diagnosis can be challenging. Celiac disease - related antibodies antibodies are produced by intestinal B cells and can be detected in the small intestinal mucosa before their appearance in serum or before mucosal damage. In this paper, we reviewed the literature concerning the diagnostic value of intestinal celiac disease - related antibodies.